Asbab al-Wurud dalam Perspektif Ilmu Hadis - Said Agil Husin Al Munawar (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 1998)
This paper specifically aims to discuss issues surrounding asbāb al-wurūd. Asbāb al-wurūd refers to the reasons or historical contexts that underlie the emergence of a hadith. Understanding asbāb al-wurūd is essential for accurately interpreting hadiths, as historical context can influence the meaning and application of the hadith. The function and relevance of asbāb al-wurūd in hadith studies are to provide a more comprehensive understanding of hadiths, help resolve contradictions between hadiths, and ensure that the interpretation of hadiths aligns with their original context. This research will explore the definition, function, and relevance of asbāb al-wurūd in hadith studies, as well as the importance of this understanding for the interpretation and application of Islamic law.